Removable Orthodontic Appliances - Vijayalakshmi K; Jaypee eBooks (Jaypee Brothers Medical Publisher (P) Ltd., 2010)
Removable appliances are fabricated in the laboratory rather than directly in the patient$1 (Bs mouth, reducing the dentist chair time and they can be made almost invisible if fabricated from clear plastic materials. This makes them more acceptable to especially adult patients. These advantages for both the patient and the dentist have ensured a continuing interest in removable appliance. With a few limitations, removable appliances are most useful for the first 2 phases of treatment and contemporary comprehensive treatment is dominated by fixed appliance. However, removable appliances remain to stay as retention appliance. Major part of malocclusion need either removable appliances or with combination of semi-fixed removable appliance. Moreover, the most of simple removable appliances are delivered by general clinicians than orthodontic specialists. One, who is handling with an understanding of how appliances function, is able to rationally design, select and use orthodontic appliances in an efficient manner for the patient. This book is useful for the undergraduates and clinicians in designing and construction of the removable appliances.s
Keywords: Orthodontics and Dentofacial Orthopedics; Electronic books